Atlas of hip surgery - Bauer, R; Kerschbaumer, F; Poisel, S; Spitzer, Gerhard (Thieme, 1996)
This beautifully illustrated atlas presents a practice-oriented, comprehensive description of hip surgery. Each procedure is divided into indications, approaches, complications, and pitfalls. Based on the authors\' extensive experience in surgery and anatomy, this atlas is useful to residents, as well as to experienced surgeons wishing to review techniques used less frequently.